Tanfīdh Manhaj (Merdeka) fī Ta‘līm al-Lughah al-‘Arabiyyah al-Ṣaff al-Sābi‘ fī Madrasah al-Mutawassiṭah al-Ḥukūmiyyah 3 Banjarmāsīn - Anwar, Amimah; Muradi, Ahmad (STIQ Amuntai, 2025)
This study discusses the implementation of the Merdeka curriculum in the Arabic language subject for seventh-grade students at Madrasah Tsanawiyah Negeri 3 Kota Banjarmasin and examines the transition process from the 2013 Curriculum to the Merdeka curriculum. It explores the challenges and obstacles faced by teachers and students, particularly during the transition to a new learning paradigm. Teachers encounter major challenges in understanding and applying the concept of Merdeka Belajar, which emphasizes project-based learning, flexibility, and differentiation. The objective of this study is to analyze the implementation process of the Merdeka curriculum in seventh-grade classes, which serve as a trial for the application of the new curriculum. This study employs a qualitative descriptive research method, with data collection techniques including observation and documentation. The research findings indicate that the implementation of the Merdeka Curriculum faces significant challenges among teachers and students. The main findings show there are obstacles in the theoretical and practical understanding and mastery of concepts, particularly in the preparation of Lesson Plans (Rencana Pelaksanaan Pembelajaran/RPP). This is exacerbated by the continued dominance of the 2013 Curriculum, which hinders students' adaptation to the Merdeka Curriculum. Specifically, this study highlights that teachers' lack of mastery in developing learning materials directly impacts the learning process.